2021
DOI: 10.1088/2053-1591/ac3e94
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ta2O5 nanoparticles by using cathode glow discharge electrolysis

Abstract: Tantalum pentoxide nanoparticles (Ta2O5 NPs) were fabricated by cathode glow discharge electrolysis (CGDE) generated between a needle-like platinum wire cathode and a tantalum foil anode in 6 g L−1 Na2SO4 electrolyte solution containing 5 mL hydrofluoric acid (HF) and 0.075 g cetyltrimethyl ammonium bromide (CTAB). The chemical structure, composition and morphology of the obtained powder were analyzed by using XRD, FT-IR, SEM/EDS, XPS and UV-vis DRS. The results found that Ta2O5 NPs with orthorhombic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The same group [126] suggested that adding CTAB only changes the growth pattern of Ta2O5 crystallites rather than influencing the composition of Ta2O5 nanoparticles using the same process. Musaka et al [52] demonstrated that the average diameter of tin nanoparticles produced by wire erosion was non-linearly dependent on the concentration of gelatin, used as a surfactant in water, with a minimum value at 2 mg/L.…”
Section: Surfactantsmentioning
confidence: 99%
“…The same group [126] suggested that adding CTAB only changes the growth pattern of Ta2O5 crystallites rather than influencing the composition of Ta2O5 nanoparticles using the same process. Musaka et al [52] demonstrated that the average diameter of tin nanoparticles produced by wire erosion was non-linearly dependent on the concentration of gelatin, used as a surfactant in water, with a minimum value at 2 mg/L.…”
Section: Surfactantsmentioning
confidence: 99%
“…Atmospheric pressure (AP) gas-liquid discharge plasma has been actively investigated for its promising application prospects in water purification [1][2][3], biomedicine [4][5][6], and materials processing [7][8][9]. However, random micro discharge channels occur easily which can lead to non-directed energy distribution leading to serious issues and adversely affecting industrial applications.…”
Section: Introductionmentioning
confidence: 99%